The last kids on earth and the Nightmare King - Brallier, Max; Holgate, Douglas (New York, New York : Viking, 2017)
Jack teams up with the evil King Wretch in order to convince his friends to stay with him instead of going in search of others who may have survived the monster apocalypse.
Keywords: Survival -- Juvenile fiction; Monsters -- Juvenile fiction; Friendship -- Juvenile fiction; Humorous fiction